Bills and coins recognition - Antonio, Bernadette (2002)
The BCR Software is designed to recognize the value of certain bills and/or coins. From a scanned image of combined bills and coins, it should be able to detect their value and thus compute the total amount. Our software will analyze the picture and compare it to our database of the values of coins and bills. Its use is most significant in systems that require money recognition such as vending machines, banks, etc. The Hough Transform is used for the pre-processing, which finds the candidate bills and coins from the scanned image . After this, the candidate objects are compared to the templates for each denomination in order to determine the value of the money. This process has 75% accuracy, depending on the quality of the scanned image.